Cymbidium huikanran (Orchidaceae; Epidendroideae), a new species from China: evidence from morphology and molecular analyses - Li, Jun; Zeng, Meng-Yao; Chen, Gui-Zhen; Li, Yuan-Yuan; Liu, Zhong-Jian; Lan, Siren (Phytotaxa, 2025)
A new species of Cymbidium (Orchidaceae) from Hubei Province, China, is described as C. huikanran, which is like C. kanran and C. faberi. Morphologically, it can be distinguished from the former by its basally non-articulate leaves, and arching, short scape; from the latter by its narrowly oblong-lanceolate sepals and narrowly ovate-lanceolate petals. Molecular analysis based on nuclear ribosomal ITS and the plastid sequences (matK and rbcL) clearly indicated that is a new species as a sister to C. faberi in C. subgenus Jensoa.